Resistensi dan Ambivalensi dalam Novel Al-Yaum Al-Maw’ud Karya Najib Kailani: Analisis Potkolonial - Hasanah, Ira Nur (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
This paper focuses on the material object of a modern Egyptian novel entitled al-Yaum al-Maw'ud by Najib al-Kylani. This novel tells the story of the struggle of the Egyptian people under the leadership of King Najmuddin Ayun against the French Crusaders led by Prince Louis. What's interesting about this novel is that there are varied resistances carried out by various groups, as well as the very strong ambivalence attitude practiced by colonial figures. Meanwhile, the formal object is postcolonial theory using the deconstruction method. This theory is based on Edward Said's claim in his work "orientalism" which has an epistemological, ontological, and axiological basis targeting colonial interests. According to Said, the West and East which are opposed in such a way have violated human values ​​and must be returned to their place. The results of the study show that the binary opposition of West and East which is always associated with civilized and backward, positive and negative, white and black, is not entirely true. This can be seen in the variety and variety of resistance given by the Egyptians and Arabs. In addition, the inappropriateness of the West's actions against the East is also reflected by the ambivalence displayed by Marseil as the French army. Thus, it means that the colonization carried out by the West in the name of itself as a superior country to the East which is considered inferior has violated human values.